NEW UZBEKISTAN IN THE WORLD'S VIEW: ACHIEVEMENTS FOR ACTIVE FOREIGN POLICY AND SOCIO-ECONOMIC COOPERATION - Hakimova Muyassar Rashidovna (International Journal on Integrated Education, 2022)
This article discusses the current active foreign policy of Uzbekistan, mutually beneficial, strategically thought-out cooperation with foreign countries, as well as a number of influential international organizations. Active relations in the cultural, educational, socio-economic, humanitarian spheres in the spirit of mutual partnership and their prospects.